1988
DOI: 10.1136/jcp.41.7.720
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of decreased penicillin sensitivity of Streptococcus pneumoniae from clinical isolates.

Abstract: SUMMARY One hundred isolates of Streptococcus pneumoniae isolated from clinical specimens over nine months were examined for sensitivity to penicillin using disc tests and minimum inhibitory concentration (MIC) studies. Four per cent of the isolates were found to have reduced sensitivity to penicillin. Penicillin and methicillin discs with 1 unit and 5 ug antibiotic, respectively, were inferior to discs with 1 Mg oxacillin, which gave results comparable with those of MIC studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Indeed, testing with penicillin disks may be hazardous because resistant isolates may appear to be sensitive. We concur with earlier workers and emphasize their recommendations [6,14,[19][20][21][22] to use disks containing 1 μg oxacillin to detect increased resistance to penicillin. The only alternate method should be MIC determination using standardized techniques.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Indeed, testing with penicillin disks may be hazardous because resistant isolates may appear to be sensitive. We concur with earlier workers and emphasize their recommendations [6,14,[19][20][21][22] to use disks containing 1 μg oxacillin to detect increased resistance to penicillin. The only alternate method should be MIC determination using standardized techniques.…”
Section: Discussionsupporting
confidence: 89%
“…Close scrutiny of the four reports showed that 1 μg oxacillin disk was used by the latter investigators in Riyadh [5], two unit penicillin disks and MIC (with no details) in two earlier studies from a teaching hospital in Riyadh [8,11] and one from Jeddah [12] did not mention the method of testing. These discrepancies led us to retest the same 358 strains of pneumococci tested by Hussein [8] using oxacillin and penicillin disks and standardized agar dilution method [6,13,14,18]. Although none of these strains were recorded earlier as RPR by two unit penicillin disks, we found that 64 (18%) were RPR and 4 (1%) as resistant to penicillin.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Penicillin resistance remains at low levels in the rest of Europe, although no recent data are available from Poland, the site of a previous focus of resistant strains (50), or from other countries of Eastern Europe. In most of the United Kingdom, the trend of the prevalence is upward, with reports of 0.1% resistance in 1977 (119), 1.3% in 1981 (271), and 4% in 1987 (199). These studies, however, are based on different populations, and extrapolations may be inappropriate.…”
Section: Note On Nomenclature and Criteria Of Resistancementioning
confidence: 97%
“…The clinical relevance of intermediate resistance to the management of meningitis and the potential importance of the distinction between intermediate and high-level resistance in the management of all pneumococcal infections demand the retention of the two subdivisions of penicillin-resistant strains. The terms intermediately resistant for pneumococci for which penicillin MICs are between 0.1 and 1.0 mg/liter inclusively and highly resistant for strains for which the MIC is .2 mg/liter may be desir- 407,1985), "increased resistance" (57,211), "moderately resistant" (84), "relatively insensitive" (108), "reduced susceptibility" (137), "decreased susceptibility" (200), "decreased sensitivity" (199), and "intermediate resistance" (275). While the choice of a name is arbitrary, the terms intermediately and highly resistant fit the biochemical and genetic concepts of a stepwise increase in penicillin resistance (238,259,283) and accommodate the concept of low-level resistance, shown also to correlate with changes in affinity of penicillin-binding proteins (103; L. McDougal and C. Thornsberry, 29th ICAAC, abstr.…”
Section: Note On Nomenclature and Criteria Of Resistancementioning
confidence: 99%